Extending the time window for intravenous thrombolysis in acute ischemic stroke using magnetic resonance imaging-based patient selection. Issue 5 (July 2019) - Ringleb, Peter; Bendszus, Martin; Bluhmki, Erich; Donnan, Geoffrey; Eschenfelder, Christoph; Fatar, Marc; Kessler, Christof; Molina, Carlos; Leys, Didier; Muddegowda, Girish; Poli, Sven; Schellinger, Peter; et al.
Background: Intravenous thrombolysis with alteplase within a time window up to 4.5 h is the only approved pharmacological treatment for acute ischemic stroke. We studied whether acute ischemic stroke patients with penumbral tissue identified on magnetic resonance imaging 4.5–9 h after symptom onset benefit from intravenous thrombolysis compared to placebo. Methods: Acute ischemic stroke patients with salvageable brain tissue identified on a magnetic resonance imaging were randomly assigned to receive standard dose alteplase or placebo. The primary end point was disability at 90 days assessed by the modified Rankin scale, which has a range of 0–6 (with 0 indicating no symptoms at all and 6 indicating death). Safety end points included death, symptomatic intracranial hemorrhage, and other serious adverse events. Results: The trial was stopped early for slow recruitment after the enrollment of 119 (61 alteplase, 58 placebo) of 264 patients planned. Median time to intravenous thrombolysis was 7 h 42 min. The primary endpoint showed no significant difference in the modified Rankin scale distribution at day 90 (odds ratio alteplase versus placebo, 1.20; 95% CI, 0.63–2.27, P = 0.58). One symptomatic intracranial hemorrhage occurred in the alteplase group. Mortality at 90 days did not differ significantly between the two groups (11.5 and 6.8%, respectively; P = 0.53). Conclusions: Intravenous alteplase administered between 4.5 and 9 h after the onset of symptoms in patients with salvageable tissue did not result in a significant benefit over placebo. (Supported by Boehringer Ingelheim, Germany; ISRCTN 71616222).